Evaluating Regional Bureaucratic Capacity In The Implementation Of Inclusive Economic Development Policies - Syafaruddin Syafaruddin (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
This study examines the capacity of regional bureaucracies to implement inclusive economic development policies within the decentralised governance framework. As developing nations increasingly prioritize inclusive growth, the effectiveness of local government institutions becomes crucial for policy success. This research evaluates the bureaucratic capacity of regional governments through multiple dimensions including human resources, institutional frameworks, financial capabilities, and coordination mechanisms. Using a mixed-methods approach combining quantitative assessments and qualitative case studies from selected regional governments, this study identifies key factors that enhance or constrain bureaucratic capacity in promoting inclusive economic development. The findings reveal significant variations in capacity across regions, with institutional quality, leadership commitment, and inter-agency coordination emerging as critical determinants of implementation effectiveness. The study provides recommendations for strengthening regional bureaucratic capacity to better serve inclusive development objectives.